Analisis Implikasi Kebijakan Dividen Terhadap Pertumbuhan Perusahaan Dan Kinerja Saham - Chandra, Andrian; Sukarta Atmadja, Iswandi (Jurnal Ilmiah Manajemen Kesatuan, 2018)
The purpose of the company is to make a profit. Therefore, the company must be able to manage both the financial performance and the company. And the company should also be able to welfare shareholders through the distribution of dividends every year. The dividend policy is the company's decision to determine how much funds are distributed to shareholders as dividends and how much funds will be held by the company. With the growth of the company and good stock performance is expected to increase corporate profits and can shareholder welfare. The purpose of this research is to know the company's business, company's profitability as measured by profitability ratio, asset management as measured by liquidity ratio and activity ratio, funding policy as measured by solvency ratio, and to know the implication of dividend policy toward company growth and stock performance. With the period of 2012-2016 (the period of 5 years). The evaluation result of this research suggests that PT. Selamat, Tbk should continue to monitor the performance of the company and the performance of these shares. In order for the company to balance the benefits of the company so that it can prosper the company for the growth of the company and shareholders for the dividend payout